Pyogenic Ventriculitis Complicating Aggregatibacter aphrophilus Infective Endocarditis: A Case Report and Literature Review - Gordon W Jung; Michael D Parkins; Deirdre Church (Canadian Journal of Infectious Diseases and Medical Microbiology)
Pyogenic ventriculitis (PV) is an uncommon, but frequently fatal infection that results from inflammation of the ventricular ependymal lining associated with a purulent ventricular system. PV has been rarely reported as a secondary complication of infective endocarditis. Prompt diagnosis and treatment with appropriate culture-directed antibiotics with adequate central nervous system penetration is crucial when managing patients who are suspected of having PV. The present study reports on a fatal case of a previously well 42-year-old alcoholic woman with infective endocarditis caused by Aggregatibacter aphrophilus, with secondary brain abscess and spontaneous rupture into the ventricles causing PV.